Making hinterland transport more sustainable a multi actor multi criteria analysis. (March 2015) - Bergqvist, Rickard; Macharis, Cathy; Meers, Dries; Woxenius, Johan
Abstract: As the key nodes in our global transport system, ports are increasingly pushed to improve the sustainability of their hinterland transport system. In this paper, we use the Multi Actor Multi Criteria Analysis to evaluate four possible measures for improving the sustainability of the ports' hinterland transport systems. This methodology allows explicitly the evaluation of criteria considered relevant by all stakeholders. The analysis shows that additional port handling costs and road pricing are the alternatives that score best overall, while modal split quota are the least preferred option.